The teacher training for curriculum ict integration contributions of latosensu for undergraduate courses - Cerny, Roseli Zen; Espíndola, Marina Bazzo de; Stein, Graziela Gomes; Rocha, Julia Maria Gerhardt da (Universidade Estadual de Campinas, 2019)
This article is part of the research on a training course for educators aimed at integrating technologies into the curriculum, offered in the distance modality. We aim to analyze if the experience of university professors as teachers of the Specialization Course in Education in Digital Culture (EECD) Course favored the incorporation of the discussion on the integration of Digital Information and Communication Technologies (ICT) in the undergraduate courses in which they work. This is a qualitative research based on the methodology of Content Analysis. Based on the answers of the professors wanted to infer that the experience in the course improved the work in the degrees where they work, with knowledge about new technological resources and pedagogical uses; the understanding that learning contexts are guiding the process of technology integration; and the articulations between Digital Culture and the teaching áreas.